Carbon Taxonomy Modelling Based on The Theory Planned Behaviour - Farhan, Ali; Wahyudi, Agus; Rahardjo, Kusuma Adi (UIN Mataram, 2024)
The increasing of human activity has an impact on the environment; waste, greenhouse gases, global warming, and climate change. This research tried to design a waste management model based on individual behavior and economic values. The approach used is a mixed method using SEM PLS as a quantitative analysis tool and descriptive analysis and literature study as a qualitative analysis. The conclusion obtained is that in the consumption behavior variables, the factors age, education, food consumption, energy consumption and residues have a positive impact on awareness of managing waste, in the waste management variables education, individual benefits and values have a significant impact on awareness of managing waste, this finding then became the basis for the development of carbon taxonomy.